PENGARUH PERGANTIAN MANAJEMEN, FINANCIAL DISTRESS, UKURAN KAP, DAN OPINI AUDIT TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2012-2016 - Nisrina Dwi Setyoastuti; Murtanto Murtanto; Yuana Jatu Nilawati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
This study aims to determine the influence of management change, financial distress, auditor firm’s size, and audit opinion to auditor switching. Auditor switching, management change, and audit opinion are measured by using dummy variable. Financial distress is using Zmijewski Model, and audit firm size is measured by using an ordinal scale based on the big or small of the audit firm.The populations in this study were companies in property and real estate sector which listed in Indonesia Stock Exchange during 2012-2016. Total of 36 samples were obtained using a purposive sampling method. Hypothesis in this research are tested by logistic regression analytical method. The result of the analysis shows that management change and financial distress have significant effect on the auditor switching. while the audit opinion and audit firm size doesn’t have significant effect on the auditor switching.